Interventions for Young Women’s STEM Interest : Targeting the Predictors Self-efficacy, Belongingness, and Career Goals - Giese, Laura ; 0000-0002-5547-9210 (Lund University, 2025)
Science, technology, engineering and mathematics, often grouped under the acronym STEM, are traditionally male dominated fields. Especially in engineering and technology, women continue to be heavily underrepresented. The lack of women in STEM poses challenges for meeting the labor market demands, for product quality due to a lack of diverse perspectives in the design process, and for gender equality. Many sectors are making efforts to increase the proportion of women, but progress is slow. One reason why women are less likely to choose STEM careers is that they have lower interest in STEM compared to men. Besides dismantling gender stereotypes that create barriers for women’s interest, research needs to create interventions that can increase women’s STEM interest as well as address predictors of such interest. Three predictors of STEM interest that have received strong empirical support from previous research are self-efficacy, belongingness, and communal career goal endorsement. This thesis aims to find further support for the relationship between these predictors and STEM interest. Furthermore, it aims to evaluate an existing intervention as well as develop and test two novel interventions targeting these predictors in order to increase young women’s interest in STEM. Study I aimed to investigate the effect of a two-day intervention for high school students by a Swedish water supply company. It investigated effects on the participating women’s interest in studying engineering, as well as on their self-efficacy, belongingness, and perceived communal career goal affordance in relation to an engineering program. Study II designed and tested two novel short interventions for high school students: a role model video of five female engineering students talking about their positive experiences with their studies, and an engineering ability quiz followed by encouraging feedback on one’s performance. The study tested if the interventions increased high school women’s belongingness and self-efficacy, and thereby their interest in studying engineering. Study III suggested an additional factor to the established agentic and communal career goals, namely environmental goals. The study tested whether environmental career goals constitute a separate factor, how important they are to primary school students, and whether they predict interest in STEM careers. Study I and II found the expected gender differences in interest in studying engineering, which were mediated by gender differences in belongingness and self-efficacy (Study I and II) and by perceived communal career goal affordance (Study I). Study I found that the intervention increased young women’s engineering self-efficacy, with the effect persisting three months later. The intervention also temporarily increased women’s belongingness and perceived communal goal affordance in engineering but did not significantly increase their engineering interest. Study IIa found that women who saw the role model video had higher belongingness for engineering than women who did not see the video. Study IIb found that the engineering ability quiz and receiving positive feedback on their performance increased women’s self-efficacy for and interest in studying engineering, but the study did not replicate the effect of the role model video. Study III found that environmental career goals constituted a separate factor, and that women had higher environmental goals than men. Having higher environmental goals predicted interest in STEM careers. However, regarding the perception of what kind of goals STEM careers allow to fulfil, perceived fulfilment of communal and agentic goals predicted interest in STEM careers, while the perceived fulfilment of environmental goals did not. Taken together, these findings suggest that targeting self-efficacy, belongingness, and career goals through interventions is a promising way to attract young women to STEM, but more research is needed on how to make effects last longer and how to more reliably affect interest through affecting its predictors.
Keywords: STEM; Engineering; Gender; Interventions; Self-efficacy; Belongingness; Career goals; STEM; Ingenjörsvetenskap; Genus; Interventioner; Kompetenstro; Tillhörighet; Karriärmål